Alterations in electroencephalographic functional connectivity in individuals with major depressive disorder: a resting-state electroencephalogram study - Wang, Yingtan; Chen, Yu; Cui, Yi; Zhao, Tong; Wang, Bin; Zheng, Yunxi; Ren, Yanping; Sha, Sha; Yan, Yuxiang; Zhao, Xixi; Zhang, Ling; Wang, Gang (Frontiers in Neuroscience, 2024)
Background: Major depressive disorder (MDD) is the leading cause of disability among all mental illnesses with increasing prevalence, the diagnosis of MDD is susceptible to interference by several factors, which has led to a trend of exploring objective biomarkers. Electroencephalography (EEG) is a non-invasive procedure which has been gradually applied to detect and diagnose MDD through some features such as functional connectivity (FC). Results: During EO, lower PLVs were found in RT-LMOC (theta, alpha, beta1, beta2) and PP-RT (beta1, beta2) in the MDD group compared with HC, while the PLVs were higher in MDD group in LT-LMOC (beta2). In the period of EC, for MDD group, there were lower theta and beta (beta1, beta2, beta3) PLVs in PP-RT, as well as lower theta, alpha and beta (beta1, beta2, beta3) PLVs in RT-LMOC. Additionally, in LMFC-RT and PP-RMOC, higher PLVs were observed in beta2. There were no significant correlations between PLV and HDRS-17 scores when checking connections with significant different PLV (all p > 0.05). Conclusion: Our study confirmed the presence of differences in FC between MDD patients and healthy individuals. Lower PLV in the connection of right temporal-left occipital cortex can be mostly observed in most of the conditions, whereas an increase in PLV can be found in MDD patients in the connections of left temporal with occipital lobe (EO), the circuits of frontal-temporal, and parietal-occipital. The trends in functional connectivity involved in this study were not correlated with the level of depression. Limitations: The study was limited by the lack of further analysis of confounding factors and follow-up data. Future studies with large-sampled and long-term designs are needed to further explore the distinguishable features of EEG FC in MDD individuals.